2010
DOI: 10.5902/198050982423
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação técnica e econômica do corte de eucalipto com <i>feller-buncher</i> em diferentes condições operacionais

Abstract: O objetivo deste trabalho foi avaliar técnica e economicamente o Feller-buncher em condições diferenciadas de colheita em florestas de eucalipto em segundo corte. A análise técnica englobou um estudo de tempos e movimentos pelo método de tempo contínuo e o rendimento operacional foi determinado pelo volume em metros cúbicos de madeira colhida. A análise econômica englobou os parâmetros do custo operacional, custo de colheita florestal e rendimento energético. A análise dos dados evidenciou que a composição da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 1 publication
1
4
1
7
Order By: Relevance
“…These percentages are similar to the results of Nascimento et al (2011), who found that 65% of the time was spent in felling the trees, with the tipping of the bundles forming a 90° angle with the planting row. The percentages are also similar to the findings of Simões et al (2010), who found an average percentage of 68.2% for this element, with the feller-buncher in an extension composed of three tree rows. Therefore, the difference between the times of this element of the work cycle can be explained by the relief categories, since the harvest was conducted in a homogeneous forest with similar climatic conditions and, especially, monitored by the same feller-buncher operator.…”
Section: Discussionsupporting
confidence: 89%
“…These percentages are similar to the results of Nascimento et al (2011), who found that 65% of the time was spent in felling the trees, with the tipping of the bundles forming a 90° angle with the planting row. The percentages are also similar to the findings of Simões et al (2010), who found an average percentage of 68.2% for this element, with the feller-buncher in an extension composed of three tree rows. Therefore, the difference between the times of this element of the work cycle can be explained by the relief categories, since the harvest was conducted in a homogeneous forest with similar climatic conditions and, especially, monitored by the same feller-buncher operator.…”
Section: Discussionsupporting
confidence: 89%
“…O número mínimo de ciclos operacionais foi calculado através de um estudo piloto com um erro amostral admissível fixado em 5%, a 95% de probabilidade (Equação 1), conforme descrito por diversos autores (FIEDLER et al, 2008;OLIVEIRA JR. et al, 2009;SIMÕES et al, 2010a;SIMÕES et al, 2010b;SIMÕES et al, 2014).…”
Section: Cálculo Do Número Amostralunclassified
“…Considerando que a colheita é uma das atividades mais onerosas da cadeia produtiva de florestas plantadas (SIMÕES et al, 2010b), fica evidente a necessidade do aperfeiçoamento constante das técnicas que visam melhorar os sistemas de colheita (MINETTE et al, 2004).…”
unclassified
“…Ganhos que são ainda mais visíveis nas atividades de colheita florestal mecanizada nas quais respondem por aproximadamente 50% dos custos totais de produção florestal (MACHADO, 2014). Concomitantemente, nas atividades que envolvem a colheita de madeira, a busca de melhorias com objetivo de atingir maior produtividade, melhor planejamento, redução de custos e competitividade no mercado é cada vez mais recorrente (FIEDLER et al, 2008;SANTOS et al, 2013a;SIMÕES et al, 2010a).…”
unclassified